Pengenalan Perangkat Jaringan untuk Perluasan Akses Internet Masyarakat Pedesaan - Muaffaq Achmad Jani; Agus Darwanto; Aidil Primasetya (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The Internet is a packet switch-based computer network infrastructure with connections between computers or transmission using cables or wireless. Cables in internet standards have various models and forms in their function as a liaison between networks with the advantage that they are more resistant to noise than wireless. Currently, the need for internet services is needed to support education and information. The internet access facilities provided have limited internet coverage. This is one of the obstacles for village residents in utilizing and using the internet to obtain information and support education. This activity was carried out in Badal Village, Ngadiluwih District, Kediri Regency. It is hoped that the results of this activity for Village residents, especially village officials can recognize and know the functions of network devices that will be used to support the expansion of internet coverage. Testing the understanding of residents by using pre-test and post-test results in an increase in knowledge.